Juvenile methylphenidate reduces prefrontal cortex plasticity via D3 receptor and BDNF in adulthood - Andersen, Susan L.; Sonntag, Kai C. (Frontiers in Synaptic Neuroscience, 2014)
Background: Early drug intervention in childhood disorders aims to maximize individual potential in the short- and long-term. Consistently, juvenile exposure to psychostimulants, such as methylphenidate (MPH), reduces risk for substance use in animals and sub-populations of individuals with attention deficit hyperactivity disorder (ADHD). We investigated the effects of MPH on brain plasticity via dopamine receptor D3 (D3R) and brain-derived neurotrophic factor (BDNF) expression in developing rats. Methods: Between postnatal days 20-35, rat pups were administered saline vehicle (Veh) or MPH (2 mg/kg), the D3R-preferring agonist ± 7-OHDPAT, or the antagonist nafadotride (0.05 mg/kg) alone, or in combination with MPH twice a day. In adulthood, subjects were challenged to Veh or cocaine (10 mg/kg for two days). The prefrontal cortex was analyzed for protein and mRNA levels of total BDNF, its splice variants I, IIc, III/IV, and IV/VI, and D3 receptors. A separate group of subjects was assessed for splice variants at 20, 35, 40 and 60 days. Results: Across age strong correlations were evident between Drd3 and Bdnf mRNA levels (r=0.65) and a negative relationship between Drd3 and exon IIc after MPH exposure (r=-0.73). BDNF protein levels did not differ between Veh- and MPH subjects at baseline, but were significantly lower in MPH-treated and cocaine challenged subjects (30.3 ± 9.7%). Bdnf mRNA was significantly higher in MPH subjects, and reversed upon exposure to cocaine. This effect was blocked by nafadotride. Furthermore, Bdnftotal and Bdnf splice variants I, IIc, III/IV, and IV/VI changed across the transitions between juvenility and late adolescence. Conclusions: These data suggest a sensitive window of vulnerability to modulations of BDNF expression around adolescence, and that compared to normal animals, juvenile exposure to MPH permanently reduces prefrontal BDNF transcription and translation upon cocaine exposure in adulthood by a D3R-mediated mechanism.